Resíduos de fiação do algodão: Utilização para síntese de adsorventes catalíticos - Savoia, Jaqueline Elisabete (2024)
The textile industry faces significant challenges due to the high generation of waste throughout the production process, stemming from the production of solid waste, which often goes unused or is not recycled, as well as the substantial volume of generated effluents. The environmental impact is exacerbated by the use of dyes, which are known for their challenging degradation. In this context, the present study proposes a sustainable approach, aiming for the cyclical utilization of solid waste from the cotton spinning process in textile industries, applied for the removal of dyes in the effluent treatment stage. The synthesis of activated carbon (AC) was conducted through activation with H3PO4, pyrolysis of cotton filter powder, and impregnation with TiO2. The adsorptive materials underwent tests for photocatalysis and adsorption, using different dispersive dyes. The results of these tests proved satisfactory under the adopted experimental conditions, achieving 60% dye removal in the adsorption process and 82% in the combined processes. Adjustments to kinetic models indicate that the reaction rate follows the pseudo-second-order kinetic model. Fitting to the Langmuir equilibrium model suggests monolayer formation, reinforcing the effectiveness of the adsorptive material. The results highlight the feasibility of using cotton filter powder as activated carbon for dye degradation, presenting a sustainable solution for textile effluent treatment.